Online 13C and 14C Gas Measurements by EA-IRMS–AMS at ETH Zürich. Issue 3 (17th October 2016) - McIntyre, Cameron P; Wacker, Lukas; Haghipour, Negar; Blattmann, Thomas M; Fahrni, Simon; Usman, Muhammed; Eglinton, Timothy I; Synal, Hans-Arno
Abstract: Studies using carbon isotopes to understand the global carbon cycle are critical to identify and quantify sources, sinks, and processes and how humans may impact them. 13 C and 14 C are routinely measured individually; however, there is a need to develop instrumentation that can perform concurrent online analyses that can generate rich data sets conveniently and efficiently. To satisfy these requirements, we coupled an elemental analyzer to a stable isotope mass spectrometer and an accelerator mass spectrometer system fitted with a gas ion source. We first tested the system with standard materials and then reanalyzed a sediment core from the Bay of Bengal that had been analyzed for 14 C by conventional methods. The system was able to produce %C, 13 C, and 14 C data that were accurate and precise, and suitable for the purposes of our biogeochemistry group. The system was compact and convenient and is appropriate for use in a range of fields of research.